2017
DOI: 10.1002/hec.3573
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spousal bereavement on hospitalisations: Evidence from the Scottish Longitudinal Study

Abstract: This paper estimates the impact of spousal bereavement on hospital inpatient use for the surviving bereaved by following the experience of 94,272 married Scottish individuals from 1991 until 2009 using a difference-in-difference model. We also consider the sample selection issues related to differences in survival between the bereaved and non-bereaved using a simple Cox Proportional-Hazard model. Before conducting these estimations, propensity score approaches are used to re-weight the non-bereaved to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Therefore, in computing the differences underlying the average effect of treatment on the treated, we use only matched untreated individuals, not all untreated individuals. This method is also used by Tseng et al (2017 ) and Tseng et al (2018) in the health economics literature when examining the health and wellbeing impacts of spousal bereavement. 9…”
Section: Empirical Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in computing the differences underlying the average effect of treatment on the treated, we use only matched untreated individuals, not all untreated individuals. This method is also used by Tseng et al (2017 ) and Tseng et al (2018) in the health economics literature when examining the health and wellbeing impacts of spousal bereavement. 9…”
Section: Empirical Methodsologymentioning
confidence: 99%
“… 9 Tseng et al (2018) argues that by combining PSM and Diff-in-Diff, the method allows to control for the unobserved factors constant in each group and the unobserved time-varying factors common to both groups. See for similar discussion ( Smith and Todd, 2005 ).…”
mentioning
confidence: 99%
“…We know the impact of grief is substantial. For example, scholars have noted physical health changes following bereavement such as higher likelihood of hospital visits and longer stays in hospital [ 68 ], or impacts on productivity and functioning at work [ 69 ]. The need for appropriate interventions is increasing in importance as populations are living longer and we know the age at which a bereavement is experienced can impact the understanding of death and experience of grief outcomes [ 5 , 9 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Scotland too, spousal bereavement correlated with earlier death, more hospital consultations and stays adding costs of £20 million annually (Stephen et al, 2015), with an added £2.0 for primary care consultations and £29.5 million annually for antidepressant use. Tseng et al (2018) found a 19.2% higher mortality rate for the bereaved than comparable non-bereaved. Ornstein et al (2019) found that 68% of surviving female spouses showed a $3500 increase in medical spending two years after death, associated with a $625 quarterly increase in Medicare expenditures, regardless of their caregiving status, the cause of death, or length of terminal illness.…”
Section: Introductionmentioning
confidence: 86%
“…In Scotland too, spousal bereavement correlated with earlier death, more hospital consultations and stays adding costs of £20 million annually (Stephen et al., 2015), with an added £2.0 for primary care consultations and £29.5 million annually for antidepressant use. Tseng et al. (2018) found a 19.2% higher mortality rate for the bereaved than comparable non-bereaved.…”
Section: Introductionmentioning
confidence: 86%